Examining the role of parasites in limiting unidirectional gene flow between lake and river sticklebacks. Issue 12 (26th August 2019) - Erin, Noémie I.; Benesh, Daniel P.; Henrich, Tina; Samonte, Irene E.; Jakobsen, Per J.; Kalbe, Martin
Abstract: Parasites are important selective agents with the potential to limit gene flow between host populations by shaping local host immunocompetence. We report on a contact zone between lake and river three‐spined sticklebacks ( Gasterosteus aculeatus ) that offers the ideal biogeographic setting to explore the role of parasite‐mediated selection on reproductive isolation. A waterfall acts as a natural barrier and enforces unidirectional migration from the upstream river stickleback population to the downstream river and lake populations. We assessed population genetic structure and parasite communities over four years. In a set of controlled experimental infections, we compared parasite susceptibility of upstream and downstream fish by exposing laboratory‐bred upstream river and lake fish, as well as hybrids, to two common lake parasite species: a generalist trematode parasite, Diplostomum pseudospathaceum, and a host‐specific cestode, Schistocephalus solidus . We found consistent genetic differentiation between upstream and downstream populations across four sampling years, even though the downstream river consisted of ~10% first‐generation migrants from the upstream population as detected by parentage analysis. Fish in the upstream population had lower genetic diversity and were strikingly devoid of macroparasites. Through experimental infections, we demonstrated that upstream fish and their hybrids had higher susceptibility to parasite infections than downstream fish. Despite this, naturally sampled upstream migrants were less infected than downstream residents. Thus, migrants coming from a parasite‐free environment may enjoy an initial fitness advantage, but their descendants seem likely to suffer from higher parasite loads. Our results suggest that adaptation to distinct parasite communities can influence stickleback invasion success and may represent a barrier to gene flow, even between close and connected populations. Abstract : This study shows how parasite‐mediated selection could promote local adaptation and population divergence in a system with natural, unidirectional migration from a low‐ to a high‐parasitized habitat. It describes for the first time a stickleback population naturally devoid of macroparasites, allowing inquiry into how parasites can prevent gene flow.